2012
DOI: 10.1186/1471-2156-13-45
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA paradox: sex-specific genetic structure in a marine mussel – despite maternal inheritance and passive dispersal

Abstract: BackgroundWhen genetic structure is identified using mitochondrial DNA (mtDNA), but no structure is identified using biparentally-inherited nuclear DNA, the discordance is often attributed to differences in dispersal potential between the sexes.ResultsWe sampled the intertidal rocky shore mussel Perna perna in a South African bay and along the nearby open coast, and sequenced maternally-inherited mtDNA (there is no evidence for paternally-inherited mtDNA in this species) and a biparentally-inherited marker. By… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…These sequences have been submitted to GenBank (accession numbers KC356872-KC357249). We compared the new sequences with 172 previously published se quences from adult P. perna (Nicastro et al 2008, Teske et al 2012. Genetic diversity indices in P. perna were mostly larger for the samples from the bay than those from the open coast, with the difference being particularly clear in the adult females (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These sequences have been submitted to GenBank (accession numbers KC356872-KC357249). We compared the new sequences with 172 previously published se quences from adult P. perna (Nicastro et al 2008, Teske et al 2012. Genetic diversity indices in P. perna were mostly larger for the samples from the bay than those from the open coast, with the difference being particularly clear in the adult females (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously suggested that the skewed sex ratio in Perna perna could be the result of post-settlement selection (Teske et al 2012). Females have greater reproductive output than males ), and mussels in bays produce more gametes than those on the open coast (McQuaid & Phillips 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure between fjords/bays and open coast has also been found in other organisms (e.g. mussels: Nicastro et al, 2008, Teske et al, 2012, including cod in the Skagerrak region (Knutsen et al, 2011). Oceanographic features, such as bathymetry, temperature, and salinity boundaries, and habitat heterogeneity may all act as barriers to population connectivity in marine species in this region (e.g.…”
mentioning
confidence: 99%